Assessing Volumetric Absorptive Microsampling Coupled with Stable Isotope Dilution Assay and Liquid Chromatography–Tandem Mass Spectrometry as Potential Diagnostic Tool for Whole Blood 5-Methyltetrahydrofolic Acid - Kopp, Markus; Rychlik, Michael (Frontiers in Nutrition, 2017)
Volumetric absorptive microsamplers (VAMS) have been developed recently as a promising tool for clinical blood sampling. Compared to dried blood spot samples analyzed by accurate stable isotope dilution assays (SIDAs), the new technique could provide further substantial miniaturizing of folate assays by eliminating hematocrit effects and uneven analyte distribution within the sample. Herein, we present a miniaturized SIDA coupled with LC-MS/MS measurement of 5-methyltetrahydrofolic acid as main folate vitamer in whole blood (WB) using [13C5]-5-methyltetrahydrofolic acid as internal standard. Elution and extraction of only 10.8 μL-dried WB were carried out by centrifugation followed by enzymatic treatment for polyglutamate deconjugation. Matrix separation was achieved by heating and centrifugation. To verify applicability, WB folate status of 11 volunteers was screened. Limits of detection and limits of quantitation were 9 and 26 nmol·L−1, respectively, which is sufficiently low for screening folate status. Recoveries were 97 (±5.8), 99 (±2.8), and 96 (±6.1)% for 800, 400, and 200 nmol L−1 5-methyltetrahydrofolic acid, respectively. Precision of the LC-MS/MS instrument and inter-assay precision trials revealed CVs of 8.1 and 3.5% (294 nmol L−1), respectively, thus confirming reproducible and precise quantitation. Compared to fresh WB, no significant degradation of 5-methyltetrahydrofolate was observed after 2.5 h of drying at room temperature. VAMS 5-CH3-H4folate was stable for at least 3 weeks at −20°C. In our pilot study, accurate and diagnostically conclusive determination of folate status was verified. Nevertheless, blood sampling should be performed by trained individuals to avoid substantial errors concerning the absorbed volume. Endogenous folate in rat serum and chicken pancreas caused a significant background especially at low blood 5-CH3-H4folate levels and, thus, for polyglutamate deconjugation, these background folates or alternative mixtures need to be removed. The superior feasibility of a minimized blood collection with VAMS allows further progress regarding time- and cost-effective methodologies in newborn or population screenings for 5-methyltetrahydrofolate status. Further steps toward minimization could include an automated assay coupled with UPLC-MS/MS.